2021
DOI: 10.1167/iovs.62.12.21
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Systemic Hypertension on the Macular Microvasculature in Diabetic Patients Without Clinical Diabetic Retinopathy

Abstract: Purpose To identify the impact of hypertension (HTN) on macular microvasculature in type 2 diabetes (T2DM) patients without clinical diabetic retinopathy. Methods In this retrospective cross-sectional study, subjects were divided into three groups: controls (control group), patients with T2DM (DM group), and patients with both T2DM and HTN (DM + HTN group). The vessel length density (VD) was compared among the groups. Linear regression analyses were performed to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…[10][11][12] Due to the location of the retinal microvasculature, mainly located in the inner retinal layer, the retinal microvasculature will be closely related to the inner retinal layer thickness, which was shown in Table 3 and also reported in previous studies. 13,14 Although the precise temporal relations cannot be known in this study, the retinal microvasculature that impaired with progressing AMD stage would be one of contributing factors associated with the inner retinal layer thinning in dry AMD.…”
Section: Discussionmentioning
confidence: 92%
“…[10][11][12] Due to the location of the retinal microvasculature, mainly located in the inner retinal layer, the retinal microvasculature will be closely related to the inner retinal layer thickness, which was shown in Table 3 and also reported in previous studies. 13,14 Although the precise temporal relations cannot be known in this study, the retinal microvasculature that impaired with progressing AMD stage would be one of contributing factors associated with the inner retinal layer thinning in dry AMD.…”
Section: Discussionmentioning
confidence: 92%
“…The basic characteristics of the included studies are summarized in Table 1, which comprised 13,773 participants and 15,416 eyes from 23 countries worldwide. In all the studies, there were participants with T2D ( n = 49), [2–6,9,19,21,26–29,32,38–73] T1D ( n = 27), [1,17,18,20,24,30–32,36,37,46,55,56,70,71,74–85] T1D/T2D mixed ( n = 9), [22,25,33,86–91] prediabetes ( n = 5) [9,10,42,92,93] and unclear ( n = 4). [16,94–96]…”
Section: Resultsmentioning
confidence: 99%
“…The potential publication bias for the variables was evaluated using Egger's test. Except for the measurements [19] 290 430 China Type 2 Unclear Foveal, parafoveal, perifoveal thickness Arias (2021) [92] 24 26 Colombia Prediabetes -FAZ area, AI Ulutas et al (2021) [74] Temel and Batioglu (2021) [86] 51 59 Turkey Li et al (2021) [6] Lee et al (2021) [3] Kocer and Sekeroglu (2021) [4] 25 29 Turkey Type 2 7.5 Retinal, foveal, parafoveal, perifoveal VD Kara and Can (2021) [37] 118 120 Turkey Type 1 4.9 Retinal, foveal, parafoveal, perifoveal VD Huru et al (2021) [9] 1638 310/57 * Finland Prediabetes/type 2 † -/unclear ‡ Foveal, parafoveal, perifoveal thickness/GCL thickness Hepokur et al (2021) [46] Endo et al (2021) [2] 62 92 Japan Type 2 10.9 Foveal VD (SCP), foveal thickness Damian et al (2021) [87] 36 38 Romania Type 1/2 mixed 10.31 SFCT Damian and Nicoara (2021) [48] 32 32 Romania Type 2 9.24 Foveal, parafoveal, perifoveal thickness/pRNFL, mRNFL, GCL thickness Chen et al (2021) [36] [5] 50 99 Turkey Type 2 9.62 Retinal, foveal, parafoveal, perifoveal VD/foveal thickness Bontzos et al (2021) [94] 54 54 Greece Unclear 4.62 Retinal VD/GCC thickness Aksoy et al (2021) [75] Unclear Foveal, parafoveal thickness/retinal, foveal, parafoveal VD Lim et al (2020) [16] 63 49 Korea Unclear 7.1 pRNFL thickness Sousa et al (2020) [1] 12.62 Foveal, parafoveal, perifoveal thickness/pRNFL thickness, SFCT Sacconi et al (2020) [18] 12 12 Italy Type 1 35 Foveal, parafoveal thickness/SFCT Pinilla et al (2020) [76] [21] Piona et al (2020) [17] 51 147 Italy Type 1 8.9 pRNFL, GCL thickness Ozturk et al (2020) [77]…”
Section: Quality and Publication Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in line with those of previous studies that showed early microvascular alterations on OCTA in DM patients. Previous studies found certain microvascular alterations prior to the onset of clinical signs of DR in DM patients [4,23]. A recent meta-analysis of data from 2,241 eyes of DM patients showed that DM patients without clinical DR had an enlarged FAZ area and decreased perfusion density in the parafoveal capillary plexus compared to healthy controls [24].…”
Section: Discussionmentioning
confidence: 96%